(3eLQHGJ aj GdWH dCfGS TJis
(3ChdgG (B:s
(3bGd OjSbhQjOhS (B: (3HRQ GdHGPhQO, LjO ddUHjGf GdPjf jYQV dge aSGO ai MQcGJ GdYVd s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg bhdg (B: (3adjLJfH GdaUO, hNGUI EP cGfJ GdYdI GdJi JbOeJ eRefI , hcGfhG bO EbJUOhG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B83 - (3U(B107s
(3GdfSNI HgG MhGTs
(3YdjgG JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs